Caridina xiangnanensis, a new freshwater atyid shrimp (Crustacea, Decapoda, Atyidae) from Hunan Province, China - Liu, Xiao-Yan; Guo, Zhao-Liang; Yu, Hui (Zootaxa, 2006)
Caridina xiangnanensis, new species is described on the basis of specimens collected from Lingxiu Village, Rucheng County, Hunan Province, China. This new species can be distiguished from the closely related species, C. paracornuta Cai & Yang, by the narrower endopod of the male first pleopod, lacking a projection on the proximal region; a longer appendix interna; a shorter appendix interna of the male second pleopod; and the comparatively narrower scaphocerite.